FAMILY SCIARIDAE - Carvalho-Fernandes, Sheila Patrícia (Zootaxa, 2016)
Sciaridae are a widely distributed family with high number of species. They are known as black fungus gnats due to their dark color and feeding activity. This catalogue presents 17 species from Colombia distributed in eight genera, and for each species the geographical distribution is provided.